Construction Of Virtual Heritage Application: Between Theory And Practice - Musa, Siti Noraishah (2010)
The objective of this research is to indicate the main element or pillar in the reconstruction of a virtual heritage application. The study will be based on the research of the virtual heritage application that has been done before by other researcher. This research also will include the comparison of the suggested elements from many points of view such as academics, developers and researcher’s observation through online application. The results are aimed to give an insight of what is the main element or pillar that can be implemented in the reconstruction process and the proposed elements can be a theory for a virtual heritage application.